SOME PROPERTIES OF M-SUBHARMONIC FUNCTIONS - Yodgarov S; Omonov O (PT. Antis International Publisher, 2024)
It is proved in the paper that if a function is -harmonic in a polydisk, then the function is -subharmonic. In addition, the case is proved to be a -harmonic function.